2013
DOI: 10.1371/journal.pone.0065219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Age at Birth on Cognitive Performance: A Function of Cognitive Workload Demands

Abstract: ObjectiveCognitive deficits have been inconsistently described for late or moderately preterm children but are consistently found in very preterm children. This study investigates the association between cognitive workload demands of tasks and cognitive performance in relation to gestational age at birth.MethodsData were collected as part of a prospective geographically defined whole-population study of neonatal at-risk children in Southern Bavaria. At 8;5 years, n = 1326 children (gestation range: 23–41 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 54 publications
3
63
0
2
Order By: Relevance
“…It has previously been reported that the relationship between gestational age and academic outcomes is not linear but curvilinear with increasingly stronger effects below 33-36 weeks [25,35,44, 45] thus we explored this possibility. Results, however, showed that effects of preterm birth on early inhibition and effects of inhibition on later outcomes were overall not stronger in the more preterm compared with the term groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported that the relationship between gestational age and academic outcomes is not linear but curvilinear with increasingly stronger effects below 33-36 weeks [25,35,44, 45] thus we explored this possibility. Results, however, showed that effects of preterm birth on early inhibition and effects of inhibition on later outcomes were overall not stronger in the more preterm compared with the term groups.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm individuals often have general cognitive impairments [35,44,46] and these are associated with their academic outcomes. Although the relationship between cognitive abilities and achievement was not the focus of this study, we explored whether the effects of early inhibitory control on childhood outcomes were explained by toddlers' cognitive abilities, assessed with the Griffiths Mental Development Scales [36] at 20 months of corrected age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy infants who were born in the same obstetric hospitals, cared for on normal postnatal wards were recruited as controls (N=916), resulting in a total study sample of 8421 newborns. Of the 8421 participants, 1513 children were selected for follow-up at 6 and 8 years of age according to the following criteria: 1. either very preterm (<32 weeks gestation) or very low birth weight (<1500g birth weight); 2. a subsample of children born at ≥32 weeks gestation randomly selected within the stratification factors gender, family SES (low, medium and high) and degree of neonatal risk (none, low, moderate, high and very high) (22).…”
Section: Study Samplementioning
confidence: 99%
“…VP/VLBW children and adolescents have an increased prevalence of cognitive deficits [1][2][3] and recent evidence indicates that young VP/VLBW adults still have lower average IQ scores compared with those born at term. 1,2,[4][5][6] It is, however, not known whether the same children who had cognitive deficits in childhood continue to have deficits in adulthood, as developmental tests in early childhood rely strongly on sensorimotor skills and may not accurately measure core cognitive ability.…”
mentioning
confidence: 99%